2021
DOI: 10.3892/etm.2021.9840
|View full text |Cite
|
Sign up to set email alerts
|

Allyl isothiocyanate increases MRP1 expression in cigarette smoke extract‑stimulated human bronchial epithelial cells via the JNK/Nrf2 pathway

Abstract: Multidrug resistance-related protein 1 (MRP1) is involved in the biological transport of several molecules with diverse structural characteristics outside of the cell. In addition to its transport activity, MRP1 exhibits multiple defense mechanisms in vivo . MRP1 is highly expressed in normal lung tissues and plays a protective role in the process of chronic obstructive pulmonary disease. In the present study, human bronchial epithelial cells (16HBE14o-cells) were stimulated by cigarette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…AITC attenuates inflammation and oxidative stress via the modulation of Nrf2/HO-1 and NF-ĸB pathways, thereby ameliorating traumatic brain injury in mice [ 156 ]. Zhang et al [ 157 ] reported that AITC elevates the expression of multidrug resistance-related protein 1 (MRP1) in cigarette smoke extract-stimulated human bronchial epithelial cells via the activation of the JNK/Nrf2 pathway. It also reduces spontaneous degradation in hepatocyte and attenuates acetaminophen-induced liver injury via the activation of Nrf2, thereby making it a potential drug for liver-related injuries [ 158 ].…”
Section: Nrf2-activating Natural Organosulfur Compoundsmentioning
confidence: 99%
“…AITC attenuates inflammation and oxidative stress via the modulation of Nrf2/HO-1 and NF-ĸB pathways, thereby ameliorating traumatic brain injury in mice [ 156 ]. Zhang et al [ 157 ] reported that AITC elevates the expression of multidrug resistance-related protein 1 (MRP1) in cigarette smoke extract-stimulated human bronchial epithelial cells via the activation of the JNK/Nrf2 pathway. It also reduces spontaneous degradation in hepatocyte and attenuates acetaminophen-induced liver injury via the activation of Nrf2, thereby making it a potential drug for liver-related injuries [ 158 ].…”
Section: Nrf2-activating Natural Organosulfur Compoundsmentioning
confidence: 99%